(untitled) (Research, Society and Development, 2022)
Allelopathy is the beneficial or harmful effect that a plant can have on another, which can occur directly or indirectly, being a phenomenon still little known in relation to native species. So with this work the objective was to verify the cytotoxic activity of the aqueous extracts and by infusion of the leaves of Matayba guianensis Aubl. on the germination and development of seedlings of Lactuca sativa L., (lettuce) and Cenchrus echinatus L., (burr), in addition to identifying the classes of secondary compounds present in these extracts. The treatments consisted of aqueous extract and extract by infusion at 25, 50, 75 and 100% of concentration and a control group (0%) consisting of distilled water. The bioassays were arranged in a completely randomized design, where each treatment consisted of five replications containing 20 seeds each. The osmotic potential and pH of the extracts were recorded at different concentrations. The experiments were carried out in a BOD germination chamber at 25ºC and a photoperiod of 12 hours for five days for burr seeds and seven days for lettuce seeds. The percentage of germination, the germination speed index (GSI), the length of the stalk and radicle and the occurrence of necrosis of the seedlings radicles were evaluated. Data were submitted to analysis of variance using the ASSISTAT 7.7 beta program. The prospection of chemical constituents was done through the staining technique. The aqueous extract of M. guianensis promoted inhibition of germination, in the germination speed index of lettuce seeds, positively affected the growth of the stem, inhibited the growth of the radicles and promoted necrosis in these when submitted to the aqueous extract at 75% of concentration. The extract by infusion did not cause any effect on seed germination, root length or necrosis, however it promoted inhibitory effects on GSI; and positive effects in relation to the growth of stems of lettuce seedlings. The aqueous extract of M. guianensis inhibited germination, GSI, stem and rootlet growth of the bur. The extract by infusion, on the other hand, did not promote significant effect on germination, GSI, growth of stems and radicles of the referred species. As for phytochemical prospection, the aqueous extract of M. guianensis leaves showed phlobaben tannins; flavones, flavonols and xanthones; chalcones, aurones and flavononols. While the infusion extract showed phenols; flavones, flavonols and xanthones; chalcones and aurones; flavononols; leucoanthocyatidines; catechins and flavonones. It is likely that the allelopathic action observed is due to the compounds identified in these extracts, requiring more effective studies to isolate them in order to verify their isolated action with a view to future use as a bioherbicide.